Post-Synthesis Optimization of Reversible Circuits - Dalcumune, Edinelço; Kowada, Luis A. B.; Figueiredo, Celina M. H. de; Marquezino, Franklin de L. (Anais do Encontro de Teoria da Computação (ETC); 2021: Anais do VI Encontro de Teoria da Computação, 2021)
One of the main motivations for reversible computing is that quantum computing has as one of its foundations the reversibility of all gates, that is, quantum computing circuit models are reversible. An important problem in reversible computing that has been intensively studied for the last decades is the synthesis of reversible circuits. The extended abstract considers optimization rules aiming to a new algorithm for post-synthesis optimization of reversible circuits composed of generalized Toffoli gates.